Coping strategies towards people with multiple sclerosis, throu-ghout their life experience - Miranda-Seguel, Verónica (Universidad de Sonora, 2019)
Introduction: Multiple Sclerosis is the most common neurological disease on the population aged 20 to 30. But it counts with scarce published qualitative and scientific evidence, and the information that could be found, does not cover the topics developed herein. Objective: Understand coping strategies through the life experience of people living with Multiple sclerosis who belong to the Corporación Pacientes Esclerosis Múltiple (Corporation of Multiple Sclerosis Patients Talca) Talca, Chile. Methodology: Descriptive phenomenological study with qualitative approach. Seven people over the age of 18 participated, who had been diagnosed with Multiple Sclerosis. Semi-structural in-depth interviews were held, selected by non probabilistic sampling of convenience until the saturation of data. Throughout the whole research, the ethical principles of Ezequiel Emanuel were respected. Results: People with Multiple Sclerosis report from their own life experience regarding coping strategies such as personal predisposition; Self-esteem and Functionality acquired through support networks (mainly family and healthcare staff). Conclusions: The life experiences of people with MS are different and vary from person to person, depending on countless bio-psycho-social factors, but, within these factors, coping strategies stand out whether they are innate or acquired, added to other characteristics such as sex and age, amongst others.